Respuesta :
Answer:
a = - 1.1
Step-by-step explanation:
Condition for a single variable function f(x) to be decreasing is f'(x) < 0.
So, in our case, [tex]f(x) = \frac{4}{x^{2}} - 6x + 9[/tex].
Then, differentiating with respect to x on both sides we get,
[tex]f'(x) = 4(- 2)\frac{1}{x^{3}} - 6 < 0[/tex]
⇒ [tex]- \frac{8}{x^{3}} - 6 < 0[/tex]
⇒ [tex]\frac{8}{x^{3}} + 6 > 0[/tex]
{Dividing both sides with - 1 and hence the inequality sign changes}
⇒ [tex]\frac{8}{x^{3}} > - 6[/tex]
⇒ 8 > - 6x³ {Multiplying both sides with x³}
⇒ 6x³ > - 8 {Interchanging the sides}
⇒ [tex]x^{3} > - \frac{8}{6}[/tex]
⇒ x > - 1.1
Therefore, a = - 1.1. (Answer)
Answer:
Just did this. The answer is 3
Step-by-step explanation: